Filem Melayu 1930an-1960an Sebagai Citra Budaya dan Sejarah Negara - Jins, Shamsudin (2010)
This research is an analysis on Malay films of the 1930s to the 1960s. The objective of this research is to determine whether the Malay films of these period portray our nation's cultural and historical perspective. Content analysis is the methodology chosen by this research, applying related sociological and historical theories. As a general overview, Malay films made their debut in Singapore in the 1930s. By the 1950s production moved to Kuala Lumpur. Malay films in this context were imbued not only with the entertainment milieu but represent our cultural and historical record. The research findings based on the 50 old Malay films chosen revealed that the films are a bundant with various cultural and historical inquiries of our nation. In Addition, the language aspect is also found to be predominant in these old Malay films. The cultural topography of the films are found to be attached to the socio-cultural, socio-political and socio-economical factors that existed concurrently within the nation's landscape that is also a projection of its assimilation of the foreign cultural influence. From the language perspective, the research discovered that the films being researched applied many mixed Malay language such as the Betawi, Riau Malay languages as well as language of the Palace courts. These films too have begun to use the mixed-language (Bahasa Rojak) of our society. The mixed-languages were found to have been used in Singapore priop to its arrival in Kuala Lumpur. Base on the analysis, it is found that the Malay old films projected historical elements in its themes, narratives, names of character and its landscape. In conclusion, the old Malay films being researched has given us an overture that it is not designated as a mere medium of entertainment but on a larger context, it is a valuable and significant medium of recording our nation's passage of the past.